2008
DOI: 10.1080/08037050802589593
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hypertension and its risk factors between the Guangxi Bai Ku Yao and Han populations

Abstract: The difference in the hypertension prevalence between the two ethnic groups might result from different diet, lifestyle, physical activity level, sodium intake and genetic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 53 publications
1
38
2
Order By: Relevance
“…Thus, Bai Ku Yao is thought to share the same ethnic ancestry and to possess a homogeneous genetic background, and is a useful subgroup for population genetic studies. In several previous epidemiological studies, we found that blood pressure levels and the prevalence of hypertension were lower in normal weight than in overweight/obese subjects [3,4]. We hypothesized that the differences in blood pressure levels between normal weight and overweight/obese subjects might partly result from different interactions of some SNPs and overweight/obesity in this population.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Thus, Bai Ku Yao is thought to share the same ethnic ancestry and to possess a homogeneous genetic background, and is a useful subgroup for population genetic studies. In several previous epidemiological studies, we found that blood pressure levels and the prevalence of hypertension were lower in normal weight than in overweight/obese subjects [3,4]. We hypothesized that the differences in blood pressure levels between normal weight and overweight/obese subjects might partly result from different interactions of some SNPs and overweight/obesity in this population.…”
Section: Introductionmentioning
confidence: 76%
“…A total of 1729 unrelated participants of Bai Ku Yao who reside in Lihu and Baxu villages in Nandan County, Guangxi, China were randomly selected from our previous stratified randomized cluster samples [3,4]. The age of the subjects ranged from 15 to 86 years, with an average age of 41.38 ± 14.71 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The individuals with TC > 5.17 mmol/L and/or TG > 1.70 mmol/L were defined as hyperlipidemic [29,30]. Hypertension was diagnosed according to the criteria of 1999 World Health Organization-International Society of Hypertension Guidelines for the management of hypertension [33,34]. The diagnostic criteria of overweight and obesity were according to the Cooperative Meta-analysis Group of China Obesity Task Force.…”
Section: Methodsmentioning
confidence: 99%
“…The individuals with TC > 5.17 mmol/L and/or TG > 1.70 mmol/L were defined as hyperlipidemic [38,39]. Hypertension was diagnosed according to the criteria of 1999 World Health Organization-International Society of Hypertension Guidelines for the management of hypertension [43,44]. The diagnostic criteria of overweight and obesity were according to the Cooperative Meta-analysis Group of China Obesity Task Force.…”
Section: Methodsmentioning
confidence: 99%